A novel missense variant c.G644A (p.G215E) of the RPGR gene in a Chinese family causes X-linked retinitis pigmentosa. Issue 10 (18th October 2019) - Fu, Jiewen; Cheng, Jingliang; Zhou, Qi; Wei, Chunli; Chen, Hanchun; Lv, Hongbin; Fu, Junjiang
Abstract: The mutations in patients with X-linked retinitis pigmentosa (xlRP) have not been well described in the Chinese population. In the present study, a five-generation Chinese retinitis pigmentosa (RP) family was recruited; targeted next-generation sequencing (TGS) was used to identify causative genes and Sanger sequencing for co-segregation. RNA-seq data analysis and revere transcriptional-polymerase chain reaction (RT-PCR) were applied to investigate gene expression patterns of RP GTPase regulator ( RPGR ) in human and Rpgr in mouse. A novel, hemizygous, deleterious and missense variant: c.G644A (p.G215E) in the RPGR gene (NM_000328.2) exon 7 of X-chromosome was identified in the proband, which was co-segregated with the clinical phenotypes in this family. RNA-seq data showed that RPGR is ubiquitously expressed in 27 human tissues with testis in highest, but no eye tissues data. Then the expressions for Rpgr mRNA in mice including eye tissues were conducted and showed that Rpgr transcript is ubiquitously expressed very highly in retina and testis, and highly in other eye tissues including lens, sclera, and cornea; and expressed highly in the six different developmental times of retinal tissue. Ubiquitous expression in different tissues from eye and very high expression in the retina indicated that RPGR plays a vital role in eye functions, particularly in retina. In conclusion, our study is the first to indicate that the novel missense variant c.G644A (p.G215E) in the RPGR gene might be the disease-causing mutation in this xlRP family, expanding mutation spectrum. These findings facilitate better understanding of the molecular pathogenesis of this disease; provide new insights for genetic counseling and healthcare.